Multiple-Electrode Switching-Based Radiofrequency Ablation vs. Conventional Radiofrequency Ablation for Single Early-Stage Hepatocellular Carcinoma Ranging From 2 to 5 Cm - Huang, Guang-liang; Liu, Ming; Zhang, Xiao-er; Liu, Bao-xian; Xu, Ming; Lin, Man-xia; Kuang, Ming; Lu, Ming-de; Xie, Xiao-yan (Frontiers in Oncology, 2020)
Purpose: To retrospectively compare the treatment outcome of multiple-electrode switching based radiofrequency ablation (switching-RFA) and the conventional RFA for early-stage hepatocellular carcinoma (HCC). Methods: A total of 122 patients with single early-stage HCC ranging from 2.1 to 5.0 cm received ultrasonography-guided percutaneously RFA as the first-line treatment. Seventy-one patients underwent switching-RFA and 51 underwent conventional RFA. Tumor response, major complication, local tumor progression (LTP) and overall survival (OS) were compared between two groups. Log-rank tests and Cox regression models were used for univariate and multivariate analysis to identify predictors of LTP and OS. Results: The rate of initial local complete response was 100% (71/71) in the switching-RFA group and 98.0% (50/51) in the conventional RFA group (P > 0.05). No major complication occurred in the switching-RFA group while two in the conventional RFA group. After a median follow-up period of 45.9 months (range, 9.8-60.0 months), the rates of LTP in the switching-RFA group and conventional RFA group were 19.7% (14/71) and 41.2% (21/51), respectively. The cumulative LTP rates at 1, 3 and 5 years were 11.3%, 20.5% and 20.5% for switching-RFA and 17.6%, 38.7% and 46.7% for conventional RFA, respectively (P < 0.001). Switching-RFA was an independent factor associated with lower LTP rate (P = 0.022). Five-year OS was 75.8% following switching RFA vs. 66.2% following conventional RFA (P = 0.363). Extrahepatic recurrence was significant prognostic factor for overall survival in multivariable analysis. Conclusion: Compared to conventional RFA, switching-RFA provides a high local tumor control for single early-stage HCC. An ongoing randomized trial might help to clarify the role of this approach for the treatment of HCC.